Ammonium ions improve the survival of glutamine-starved hybridoma cells. Issue 1 (December 2016) - Abusneina, Abdelmuhsen; Gauthier, Eric
Abstract Background As a consequence of a reprogrammed metabolism, cancer cells are dependent on the amino acidl -glutamine for their survival, a phenomenon that currently forms the basis for the generation of new, cancer-specific therapies. In this paper, we report on the role which ammonium ions, a product of glutaminolysis, play on the survival ofl -glutamine-deprived Sp2/0-Ag14 mouse hybridoma cells. Results The supplementation ofl -glutamine-starved Sp2/0-Ag14 cell cultures with either ammonium acetate or ammonium chloride resulted in a significant increase in viability. This effect did not depend on the ability of cells to synthesizel -glutamine, and was not affected by the co-supplementation with α-ketoglutarate. When we examined the effect of ammonium acetate and ammonium chloride on the induction of apoptosis by glutamine deprivation, we found that ammonium salts did not prevent caspase-3 activation or cytochrome c leakage, indicating that they did not act by modulating core apoptotic processes. However, both ammonium acetate and ammonium chloride caused a significant reduction in the number ofl -glutamine-starved cells exhibiting apoptotic nuclear fragmentation and/or condensation. Conclusion All together, our results show that ammonium ions promote the survival ofl -glutamine-deprived Sp2/0-Ag14 cells and modulate late-apoptotic events. These findings highlight the complexity of the modulation of cell survival byl -glutamine, and suggest that targeting survival-signaling pathways modulated by ammonium ions should be examined as a potential anti-cancer strategy.